Effects of Attentional Strategies on Novice Dart Throwing, Quiet Eye Duration and Pupillary Responses. Issue 1 (2nd January 2022) - Simpson, Thomas; Ellison, Paul; Marchant, David; Carnegie, Evelyn
Abstract: This study examined the effects of focus of attention (FOA) instructions on learning a dart throwing task, quiet eye duration (QED) and pupillary responses. Thirty-six novices (M age = 33.6, SD = 19.7) learned using either (a) internal-focus (arm movement), (b) external-focus (target/dart) or (c) control instructions before completing retention and transfer tests 10 days later. FOA strategies did not significantly benefit dart throwing learning or performance. QED was associated with performance in the transfer task, and pupillary constriction occurred during the QED. The content of FOA instructions may have limited anticipated performance benefits and reduced the FOA influence on QED. Pupillary constriction reflected increased cognitive effort during QED, suggesting an important feature of future precision aiming research.